A heat pump coupled with photovoltaic thermal hybrid solar collectors: A case study of a multi-source energy system. (1st November 2017) - Emmi, Giuseppe; Zarrella, Angelo; De Carli, Michele
Highlights: The work focuses on the multi-source energy systems for the heating of buildings. Air, solar and ground sources for the heat pump are analysed. A model for the photovoltaic thermal hybrid solar collector has been developed. Integrated computer simulations of different configurations have been carried out. The solar-air sources system is the best solution for the case study. Abstract: The development of heat pump technology in the residential sector can lead, and has led to a reduction in greenhouse emissions and enhanced exploitation of renewable energy sources, including solar energy which represents the renewable source for excellence. The current study examines a multi-source energy system equipped with photovoltaic thermal hybrid solar collectors, two storage tanks for the heat source and the domestic hot water respectively and heat pumps for the space heating and domestic hot water production of a single-family dwelling located in North East Italy. Air, solar, and ground source heat pumps were analysed. Some configurations were investigated utilizing computer simulations based on a mathematical model developed to evaluate the electrical and thermal performances of hybrid solar collectors. A smart control unit capable of identifying the best heat source for the heat pump and of considering the possibility of injecting heat harvested by solar collectors into the ground during the summer period was analysed. The investigation uncovered that the multi-energy source systems were responsible for increasing the energy efficiency by 16–25% with respect to an ordinary air to water heat pump system. The simulations also revealed that the energy efficiency of the air-solar source system was slightly lower than that linked to the other configurations including a ground source heat pump.